Analytical method for the evaluation of the residual service life of prestressed concrete beams subjected to corrosion deterioration. (5th October 2021) - Franceschini, Lorenzo; Vecchi, Francesca; Belletti, Beatrice; Andrade, Carmen; Peiretti, Hugo‐Corres
Abstract: Since catastrophic failures caused by corrosion deterioration have been observed worldwide, nowadays a key research topic consists in the reliable prediction of the long‐term performance of corroded reinforced concrete structures. In this article, firstly, a refined model for the assessment of the residual service life of prestressed concrete (PC) beams has been presented. The analytical model, according to the most recent formulations proposed in the scientific literature, allows to take into account the effects induced by corrosion over time in the calculation of bending, shear, and anchorage resistances. Secondly, a case study concerning a PC beam without transversal reinforcement, exposed to wet‐dry cycles using seawater, has been presented considering the spatial variability of corrosion. To this aim, a constant and a varying spatial distribution of corrosion have been assumed. Finally, the residual service life values, evaluated according to the two assumed spatial distributions of corrosion in strands, have been compared. The proposed model can be used for the prediction of the possible failure modes of PC beams over time, considering both the reduction of the mechanical properties of the prestressing steel and the bond degradation due to corrosion deterioration according to recent experimental evidence.